Examining the Impact of Emancipated Curriculum on EFL Teachers’ Creativity in Lesson Planning and Teaching Practice at Vocational High School, Semarang Regency, Central Java - Nimas Ulfatuz Zahro Maro; Januarius Mujiyanto; Puji Astuti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines how English as a Foreign Language (EFL) teachers at SMK Negeri 1 Pringapus design and implement creative teaching practices under the Emancipated Curriculum (Kurikulum Merdeka), utilizing Torrance's (1962) framework of creativity, which encompasses fluency, originality, elaboration, and flexibility. Employing a qualitative single-case study design, data were collected through interviews, classroom observations, and analysis of lesson plans from three EFL teachers with varying backgrounds. Thematic analysis revealed that the Emancipated Curriculum provides significant space for teacher autonomy and creativity, particularly in differentiated instruction, integration of digital tools, and student-centered activities. However, the level of curriculum alignment and creativity varied among teachers, influenced by their pedagogical readiness and openness to innovation. Teachers who embraced differentiated strategies and technological tools demonstrated higher levels of creative fluency and flexibility, while others maintained conventional approaches with limited adaptation. These findings indicate that while the Emancipated Curriculum has the potential to foster innovation, effective implementation requires ongoing professional support. The study offers insights into the critical role of teacher agency and reflective practice in realizing meaningful curriculum transformation.